PENGEMBANGAN ILMU DAKWAH (Tinjauan Permasalahan Penelitian) - Nawawi Nawawi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
Formerly, da ’wa was a non academic activity. Nowadays it has developed into an academic study. As an academic study, da’wa can be differently formulated according to its thinker.In a research, da’wa study should widen the area of research including socio cultural and geographical areas. Such a research needs researchers who are capable and understand Islamic teachings, its history and development in the research location. Da ’wa researches should be promoted to develop da’wa knowledge and national development. The existence of Islam is determined by Islamic da’wa and it needs research methodology development.